Fase de fabricación, pruebas y suministro de 1113 tableros eléctricos para las viviendas de zonas no interconectadas del Municipio De Maicao – La Guajira (2023)
WEG Colombia S.A.S. is a multinational company, headquartered in Jaragua do Soul, Brazil, and based in Bogota, Colombia officially established in the Colombian electricity sector since 2014 after the purchase of FTC Energy Group company that operates in the manufacture and assembly of electrical panels for process automation. The development of the company in recent years has allowed it to enter as a high quality supplier for energy transition projects framed in the development plans of the last two governments, which is how the opportunity to participate as a supplier in a project of Non-Interconnected Zones in the department of La Guajira, particularly in the area covering the municipality of Maicao, in order to bring renewable energy to 1113 indigenous families, who have never had an electricity supply. Thus arises the project named Phase of Manufacture, Testing and Supply of 1113 Solar Boards for Homes in Non-Interconnected Zones of the Municipality of Maicao - La Guajira, whose objective is focused on supplying 1113 solar boards, with photovoltaic solar energy source and that will allow the management process of the electric energy generated by the solar panels, incorporating a storage system in lithium batteries, until the final energy consumption of the user. This document contains all the processes of initiation, planning, execution, monitoring, control and closure of the project, as well as all the tools implemented in each management plan, matrices, formats and evidence of the product with its corresponding annexes.